2021
DOI: 10.15244/pjoes/132635
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Distribution of Groundwater Composition in Deep Aquifer of Satkhira Municipality, Bangladesh

Abstract: Satkhira Municipality is located in the extreme South-Western coastal region of Bangladesh. This area exhibits complex hydro-geochemical characteristics along with the increasing tendency of soil and water salinity which created a need of groundwater quality assurance. The objectives of the study were to identify the composition of groundwater followed by attempts to investigate spatial distribution pattern of groundwater quality. This was done to identify places with the availability of best quality of drinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Besides, Bangladesh experience altered rainfall patterns and increased flood frequency that causes saltwater intrusion in coastal regions, which consequently contaminate GW resources [ 59 ]. Numerous studies have recently confirmed the degradation of WQ in various coastal regions of Bangladesh, including Satkhira [ 60 ], Khulna [ 61 , 62 ], Patuakhali [ 63 ], Gopalganj [ 64 , 65 ] and Jashore [ 66 ]. However, being the only island district of Bangladesh, the GW resources of Bhola have gained lesser attention of the scientific community in terms of rating GW state.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Bangladesh experience altered rainfall patterns and increased flood frequency that causes saltwater intrusion in coastal regions, which consequently contaminate GW resources [ 59 ]. Numerous studies have recently confirmed the degradation of WQ in various coastal regions of Bangladesh, including Satkhira [ 60 ], Khulna [ 61 , 62 ], Patuakhali [ 63 ], Gopalganj [ 64 , 65 ] and Jashore [ 66 ]. However, being the only island district of Bangladesh, the GW resources of Bhola have gained lesser attention of the scientific community in terms of rating GW state.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous types of research have been performed to verify the water quality in different coastal parts of Bangladesh, e.g., Satkhira [8,24,28], Khulna [29,30], Patuakhali [31], Gopalganj [32,33], Jashore [7,[34][35][36][37][38][39][40], and central south parts of Bangladesh [31,41]. Not only has those, but also the water quality been determined in other parts of The changing climate may have impinged on the cropping pattern of Bangladesh from the primeval period [6].…”
Section: Introductionmentioning
confidence: 99%